Book review: "... SEE LIVE PEOPLE...": TIMES, CITIES, EVENTS EYES OF THE HISTORIAN [Turchenko F. G. Before the challenges of the era. Memoirs of a historian. Zaporozhye: Helvetica Publishing House, 2023. 400 p.] - Chornyi , Dmytro (V. N. Karazin Kharkiv National University Bulletin History of Ukraine. Ukrainian Studies: Historical and Philosophical Sciences, 2024)
Book review: "... SEE LIVE PEOPLE...": TIMES, CITIES, EVENTS EYES OF THE HISTORIAN [Turchenko F. G. Before the challenges of the era. Memoirs of a historian. Zaporozhye: Helvetica Publishing House, 2023. 400 p.]